From Fringe to Formalisation: An Experiment in Fostering Interactive Public Service Media. Issue 1 (May 2015) - Hutchinson, Jonathon
The role assumed by institutions that directly develop and support online communities has emerged as a crucial factor in the development of self-governance models for online communities engaging in collaborative practices. Commonly, online communities reject top-down governance models in favour of a meritocracy that positions users in authoritative positions because of their online performance. Scholarly research into online communities suggests that their governance models are horizontal, even where the community platforms are being developed or supported by commercial institutions. Questions of authority and power emerge when institutional, top-down governance models intersect with online community meritocracy in day-to-day communicative activities and while engaging in creative production. This article examines an experiment in fostering interactive public service media by users of the now-defunct ABC Pool through the case study of Ariadne. It tracks how early user-driven ideas for creativity were aligned with the interests of the Australian Broadcasting Corporation through a process of community self-governance alongside cultural intermediation.